Cell spheroids as a versatile research platform: formation mechanisms, high throughput production, characterization and applications. (8th April 2021) - Decarli, Monize Caiado; Amaral, Robson; Santos, Diogo Peres dos; Tofani, Larissa Bueno; Katayama, Eric; Rezende, Rodrigo Alvarenga; Silva, Jorge Vicente Lopes da; Swiech, Kamilla; Suazo, Claudio Alberto Torres; Mota, Carlos; Moroni, Lorenzo; Moraes, Ângela Maria
Abstract: Three-dimensional (3D) cell culture has tremendous advantages to closely mimic the in vivo architecture and microenvironment of healthy tissue and organs, as well as of solid tumors. Spheroids are currently the most attractive 3D model to produce uniform reproducible cell structures as well as a potential basis for engineering large tissues and complex organs. In this review we discuss, from an engineering perspective, processes to obtain uniform 3D cell spheroids, comparing dynamic and static cultures and considering aspects such as mass transfer and shear stress. In addition, computational and mathematical modeling of complex cell spheroid systems are discussed. The non-cell-adhesive hydrogel-based method and dynamic cell culture in bioreactors are focused in detail and the myriad of developed spheroid characterization techniques is presented. The main bottlenecks and weaknesses are discussed, especially regarding the analysis of morphological parameters, cell quantification and viability, gene expression profiles, metabolic behavior and high-content analysis. Finally, a vast set of applications of spheroids as tools for in vitro study model systems is examined, including drug screening, tissue formation, pathologies development, tissue engineering and biofabrication, 3D bioprinting and microfluidics, together with their use in high-throughput platforms.